Pre-play communication in Cournot competition: An experiment with students and managers - Israel Waichman; Till Requate; Ch'ng Kean Siang (Kiel University, Department of Economics, 2010)
This study investigates the impact of pre-play communication on the outcomes in Cournot duopoly and triopoly experiments, using both students and managers as subjects. Communication is implemented by two different devices, a 'standardized-communication' and a free-communication device. We find that the effect of communication on collusion is larger in duopoly than in triopoly. Moreover, managers behave in a similar way under the two communication devices, while students are more influenced by the free-communication than by the standardized-communication device. In addition, managers select lower aggregate quantities than students, and communication enhances the difference between the subject pools in duopoly but reduces this difference in triopoly. Inspecting individual behavior, in all treatments the output adjustment is significantly correlated with the previous round's best response strategy. In the treatments with communication, the effect of imitation becomes larger and crowds out the effect of myopic best response. Finally, in all treatments duopoly results in more collusion than triopoly.
Keywords: L13; C93; C72; D43; D21; 330; artefactual field experiment; subject pools; Cournot oligopoly; managers; cheap talk; Oligopol; Spieltheorie; Kommunikation; Wettbewerbsbeschränkung; Feldforschung; Studierende; Führungskräfte